1990
DOI: 10.1007/bf00004498
|View full text |Cite
|
Sign up to set email alerts
|

Production, nutrient dynamics and initial decomposition of floating leaves of Nymphaea alba L. and Nuphar lutea (L.) Sm. (Nymphaeaceae) in alkaline and acid waters

Abstract: Production, turnover and nutrient dynamics of floating leaves of Nymphaea alba L. and Nuphar lutea (L.) Sm. were studied in four aquatic systems in The Netherlands, differing strongly in water quality. Production was 108-447 g AFDW.m -2 for N. lutea and 319-348 g AFDW.m 2 for N. alba. Turnover ranged from 3.6 to 4.4 without much difference between the sites and the species. During senescence 60-70% of the N and P from the leaves was resorbed by both of the plant species. The nutrient flow from the floating lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 26 publications
2
33
1
1
Order By: Relevance
“…This is in agreement with previous findings for N. lutea (Wallace, and O'Hop 1985;Kok et al 1990;Larmola et al 2003). However, in this study average daily CO 2 fluxes were higher than those reported for another site , the differences being attributable to different climatic conditions and length of the vegetative period.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with previous findings for N. lutea (Wallace, and O'Hop 1985;Kok et al 1990;Larmola et al 2003). However, in this study average daily CO 2 fluxes were higher than those reported for another site , the differences being attributable to different climatic conditions and length of the vegetative period.…”
Section: Discussionsupporting
confidence: 93%
“…The net carbon fixation estimated through the leaf production resulted in values comparable to those reported by Wallace and O'Hop (1985) and Kok et al (1990), and higher than those obtained from our CO 2 flux measurements, as also reported by Larmola et al (2003). The gap between the two methods is presumably due to the fact that CO 2 fluxes measured with floating chambers are determined by the interaction of co-occurring processes (i.e., CO 2 uptake by leaves, photo-respiration by plants, and CO 2 production and release from sediments and water column).…”
Section: Discussionsupporting
confidence: 81%
“…Deep locations were dominated by Nuphar, while the middle zones were more heavily populated by Hippuris. Both species have softer stems and leaves than do Carex and, therefore, generally have higher decomposition rates (Brock et al, 1985;Kok et al, 1990;Kok and van der Velde, 1994). Thus, SRPs in middle and deep locations should have been higher in the fall because decomposition of Nuphar and Hippuris was greater after senescence.…”
Section: Water Characteristicsmentioning
confidence: 94%
“…In addition, the decomposition of aquatic macrophytes is usually characterized by plant material gradually entering senescence and initial decay stages without first drying (Kok et al, 1990). Therefore, fresh Nuphar leaves and petioles were used for the litter bags.…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…TsUCHIYA (1989) reported that under different nutrient levels the biomass turnover of Hydrocharis dubia L. was little affected by nutrient concentration, whereas maximum biomass and net production differed markedly depending on the nutrient level. KOK et al (1990) also reported that the mean life span and the turnover rates of floating leaves in Nuphar lutea (L.) Sm. and Nymphaea alba L. were little affected by environmental factors in the various systems.…”
Section: Introductionmentioning
confidence: 95%